Implementation of technical vocational subject in Gutu East Secondary schools. - Mudzana, Eneres (Midlands State University, 2017)
The study sought to analyze how Technical Vocational subjects are implemented in Gutu East Secondary Schools aswell as ways of enhancing effective implementation of Technical Vocational subjects such that it produces employable and self reliant school graduates. The study was motivated by the increasing numbers of school leavers who are unemployed and cannot sustain themselves through use of locally available resources. 20 secondary schools were identified in Gutu East and from which four schools were randomly sampled. Participants include four heads of schools that offer Technical Vocational subjects, 40 Technical Vocational school pupils and 12 Technical Vocational teachers. Pupils and schools were randomly sampled while heads and teachers were purposively sampled. A questionnaire was used to collect data from pupils. Structured interviews were used to collect data from school heads and Technical Vocational teachers. It was revealed through this study that there are a lot of constraints to effecting implementations of Technical Vocational subjects in Gutu East Secondary Schools. According to the findings these challenges include poor funding, shortage of human resources, material resources aswell as negative attitudes of pupils. According to the findings, school leavers fail to get employment or to organize self reliant project due to poor skills acquired during years of schooling, negative attitudes towards manual labour, poor ‘O’ level results as well as lack of funding to start projects. It was concluded that implementation of Technical Vocational subjects in Secondary Schools is faced with a lot of challenges. It was therefore recommended that the government should invest heavily in capacity building of those implementing Technical Vocational subjects. Schools should form projects to generate funds to help sustain the Technical Vocational education. Exchange projects between industry and school through attachments should be offered by the Ministry Of Education as well as offering entrepreneurial skills to Technical Vocational students so that they are capable of managing self help enterprises.